EXISTENCE OF CRIMINAL LAW ON DEALING CYBER CRIME IN INDONESIA - Ranty Mahardika Jhon (IJCLS (Indonesian Journal of Criminal Law Studies), 2018)
Cybercrime is a social phenomenon that opens the scientific horizons in the world of law, how a very terrible crime can be done by just sitting sweet in front of the computer. Cybercrime is a dark side of the advancement of information and communication technology that brings widespread implications in all areas of life as they are closely linked to economic crime and organized crimes. From several types of cybercrime, UN Congress X in Vienna established hacking as first crime. The question is whether a positive criminal law can reach cybercrime, there are at least two discourses developed among criminal law experts. First, cybercrime is not a new crime and is still affordable by the Criminal Code to deal with it. In this view the arrangement to deal with cybercrime should be integrated into the Criminal Code and not in its own laws. Secondly, this opinion states the need for renewal of criminal law by forming a new law governing cybercrime. This is based on the fact that this crime has characteristics different from conventional crime, while the existing criminal law instruments are still difficult to cope with the development of this crime. There are two interesting things to look at. First, the development of Information Technology and cybercrime. Second, concerning the existence of Positive Criminal Law in handling cybercrime in Indonesia.